1971
DOI: 10.1159/000230558
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response in Rabbits Following Intranasal and Parenteral Administration of Birch Pollen

Abstract: Rabbits given birch pollen intranasally responded by forming serum and nasal antibody and also by developing immediate skin reactivity. The components of birch pollen which were mainly responsible for the development of immediate skin reactivity were identical with the components which are allergenic in man. In contrast, parenterally immunized rabbits, developed skin reactivity against allergenic as well as non-allergenic pollen components. These results suggest that allergenicity of a substance is not solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Rabbits immunized intranasally produced hemagglutinating antibodies to the non-allergenic fractions, but reaginic antibodies only to the allergenic fractions of birch pollen (6). As expected, IgG ab responses to the allergenic fractions were significantly higher in the hyposensitized group than in the untreated one.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Rabbits immunized intranasally produced hemagglutinating antibodies to the non-allergenic fractions, but reaginic antibodies only to the allergenic fractions of birch pollen (6). As expected, IgG ab responses to the allergenic fractions were significantly higher in the hyposensitized group than in the untreated one.…”
Section: Discussionsupporting
confidence: 71%
“…Belin & Strannegard (6) demonstrated that in rabbits transmucosal immunization resulted in formation of reaginic antibodies only against allergenic antigens of birch pollen, while both the allergenic and the non-0105-4538/80/010057-08 S02.50/0 allergenic antigens induced immediate hypersensitivity when administered parenterally. In the present work immune response against fractionated antigens of birch pollen was studied in man.…”
mentioning
confidence: 99%
“…It has recently been shown that the non-allergenic thermolabile BP antigens are equally capable of evoking immediate skin reactions in rabbits as are the ther mostable allergenic antigens, provided the animals are immunized by a parenteral route [4]. On the other hand, intranasal administration of BP resulted in development of immediate skin reactivity only to the heat stable, allergenic BP antigens.…”
Section: Discussionmentioning
confidence: 99%
“…As shown earlier [Strannegard and Yurchision, 1969b;Stranne gard, 1971;Belin and Strannegard, 1971] it was possible to induce reagin formation by administration of antigen via different routes. It was of particular interest that such low doses as 1 fig Hey, given intrave nously, or 30 fig birch pollen administered repeatedly intranasally, were able to induce reagin production.…”
Section: Discussionmentioning
confidence: 75%